VOLUNTEERING AS A MECHANISM FOR OVERCOMING THE SOCIAL APATHY OF YOUTH - O. Kulikova (Вестник университета, 2018)
The article is devoted the problem of overcoming social apathy of youth. The relevance of the topic is reasoned. The approaches to understanding the social apathy and reasons for it's occurrence, the forms of social activity and types of volun -teering are discussed. The results of social researches of young people’readiness to volunteering are given in the article, role of volunteering for youth is identified. Also determines main components of volunteering. The recommendations for engaging youth to volunteering are given.